Interventions to enhance the core competencies of clinical nursing preceptors: a protocol for a systematic review - Qirong Chen; Ke Liu; Xirongguli Halili; Minhui Liu; Shuyi Wang (BMJ Open)
Introduction Clinical nursing preceptors (CNPs) teach nursing skills to students in real medical scenarios and develop their professionalism. The adequacy of CNPs’ teaching competencies affects the effectiveness of student learning, so it is crucial to seek the best evidence for teaching competency interventions. This report describes a protocol for a systematic review to identify and analyse interventions to enhance the teaching competencies of CNPs. The aims of this systematic review are to (1) summarise the characteristics, quality, effectiveness and limitations of existing intervention programmes that support or train CNPs in teaching competencies; and (2) identify knowledge gaps related to teaching competencies interventions for CNPs, thereby supporting future research on constructing and improving preceptor intervention programmes.Methods and analysis This protocol follows Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) Protocols 2015 checklist. We will report this systematic review following the updated PRISMA 2020 checklist. Between 1 May 2024 and 30 May 2024, we will search PubMed, Web of Science, CINAHL, MEDLINE, EMBASE and ProQuest (Health & Medical Collection). The intervention studies that focus on enhancing and supporting the core competencies of CNPs will be included. The two researchers will conduct the study screening, data extraction and quality appraisal independently. Disagreements will be addressed by discussion or the involvement of a third researcher. We will evaluate the quality of the included studies using the modified Educational Interventions Critical Appraisal Tool. Furthermore, we will label the training programme levels using Kirkpatrick’s Four Levels of Training Evaluation Model.Ethics and dissemination Ethical approval is not applicable to this study. We will share the findings from the study at national and/or international conferences and in a peer-reviewed journal in the field of nurse education.